Evaluation of the shear bond strengths between two alternative metal alloys and porcelain (Mustansiria Dental Journal, 2018)
The success of metal-ceramic restorations is influenced by the compatibilitybetween base metal alloys and porcelains. Although porcelain manufacturersrecommend their own metal systems as the most compatible for fabricating metalceramicprostheses, a number of alloys have been used. The purpose of this study wasto evaluate the bond strength of CoCr alloy (Wironbond C) and NiCr alloy (Wiron 99)using shear forces at the metal-ceramic interface. A stainless steel cylindrical matrixwas used for preparation of the metal dies, application of ceramic and to perform theshear tests. Ten metal dies of each alloy were made for each alloy, and the metallicportion was obtained with the lost wax casting technique with standardized waxing of6.5mm of height and of 6mm of diameter. The ceramic was applied according to themanufacturer’s recommendations with the aid of a Teflon matrix that allowed itsdimension to be standardized in the same size as the metallic portion, and shear testswere performed in a universal testing machine at a cross-head speed of 0.5mm/min.The mean shear bond strength values were 53.06MPa for Wirobond C alloy, withstandard deviation of 10.67, and 45.38MPa for Wiron 99, with standard deviation of9.01. No statistically significant difference was observed between the shear strengthof the two metal-ceramic alloys.